Gene therapy for patients with advanced solid tumors: a phase I study using gene electrotransfer to muscle with the integrin inhibitor plasmid AMEP. (3rd July 2017) - Spanggaard, Iben; Dahlstroem, Karin; Laessoee, Line; Hansen, Rasmus Hvass; Johannesen, Helle Hjorth; Hendel, Helle Westergren; Bouquet, Céline; Attali, Pierre; Gehl, Julie
Abstract: Background: Gene electrotrotransfer describes the use of electric pulses to transfer DNA to cells. Particularly skeletal muscle has potential for systemic secretion of therapeutic proteins. Gene electrotransfer to muscle using the integrin inhibitor plasmid AMEP (Antiangiogenic MEtargidin Peptide) was investigated in a phase I dose escalation study. Primary objective was safety. Material and methods: Patients with metastatic or locally advanced solid tumors, without further standard treatments available, were treated with once-only gene electrotransfer of plasmid AMEP to the femoral muscle. Safety was monitored by adverse events registration, visual analog scale (VAS) after procedure and magnetic resonance imaging (MRI) of treated muscles. Pharmacokinetics of plasmid AMEP in plasma and urine was determined by quantitative polymerase chain reaction. Response was evaluated by positron emission tomography–computed tomography (PET–CT) scans. Results: Seven patients were enrolled and treated at dose levels from 50 to 250 μg of plasmid AMEP, the study was terminated early due to cessation of plasmid production. Minimal systemic toxicity was observed and only transient mild pain was associated with the delivery of the electric pulses. MRI of the treated muscles revealed discrete intramuscular edema 24 h after treatment. The changes in the muscle tissue resolved within 2 weeks after treatment. Peak concentrations of plasmid AMEP was detected only in plasma within the first 24 hours after injection. Protein AMEP could not be detected, which could be due to the limit of detection. No objective responses were seen. Conclusions: Gene electrotransfer of plasmid AMEP was found to be safe and tolerable. No objective responses were observed but other DNA drugs may be tested in the future using this procedure.